2020
DOI: 10.1002/aenm.201902085
|View full text |Cite
|
Sign up to set email alerts
|

Membrane‐Free Zn/MnO2 Flow Battery for Large‐Scale Energy Storage

Abstract: The traditional Zn/MnO2 battery has attracted great interest due to its low cost, high safety, high output voltage, and environmental friendliness. However, it remains a big challenge to achieve long‐term stability, mainly owing to the poor reversibility of the cathode reaction. Different from previous studies where the cathode redox reaction of MnO2/MnOOH is in solid state with limited reversibility, here a new aqueous rechargeable Zn/MnO2 flow battery is constructed with dissolution–precipitation reactions i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
126
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 138 publications
(126 citation statements)
references
References 51 publications
0
126
0
Order By: Relevance
“…In addition, it was confirmed that protons help promote the dissolution of MnO 2 in the discharge process and reduce the cell overpotential. [ 78 ] This work demonstrated exciting features of the cathode Mn 2+ /MnO 2 deposition/stripping charge storage mechanism and the importance of electrolyte management for the development of the Mn‐based batteries.…”
Section: Aqueous Mn‐based Batteries With Mn2+/mno2 Chemistrymentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, it was confirmed that protons help promote the dissolution of MnO 2 in the discharge process and reduce the cell overpotential. [ 78 ] This work demonstrated exciting features of the cathode Mn 2+ /MnO 2 deposition/stripping charge storage mechanism and the importance of electrolyte management for the development of the Mn‐based batteries.…”
Section: Aqueous Mn‐based Batteries With Mn2+/mno2 Chemistrymentioning
confidence: 99%
“…Therefore, further research is needed to improve the overall electrochemical performance and lower the cost of the conventional MnO 2 ‐Zn flow battery. In these regards, Cui and coworkers [ 78 ] developed a membrane‐free MnO 2 ‐Zn flow battery by circulating the single electrolyte, instead of the separated catholyte and anolyte in the conventional flow battery, through one tank without using the relatively expensive ion selective membrane (Figure 5b). The membrane‐free MnO 2 ‐Zn flow battery was conducted by the cathode Mn 2+ /MnO 2 reactions on carbon felt and the anode Zn 2+ /Zn reactions on Zn foil in the electrolyte of 1 m ZnSO 4 and 1 m MnSO 4 .…”
Section: Aqueous Mn‐based Batteries With Mn2+/mno2 Chemistrymentioning
confidence: 99%
See 3 more Smart Citations